Narrating sexual identities in Kenya: "Choice, " value, and visibility. Issue 2 (3rd April 2017) - Zingsheim, Jason; Goltz, Dustin Bradley; Murphy, Alexandra G.; Mastin, Teresa
ABSTRACT: This article examines the discursive construction of female same-sex sexual identities in Nairobi. We identify the discursive forces of "choice, " devaluation, and invisibility as influential within Kenyan media representations of lesbian, gay, bisexual, transgender, and intersex citizens. Using creative focus groups and participant observation, we demonstrate how same-sex attracted women in Nairobi resist and rearticulate these discursive forces to assert their identity and agency as individuals and as a queer community.